Impaired NGF/TrkA Signaling Causes Early AD-Linked Presynaptic Dysfunction in Cholinergic Primary Neurons - Latina, Valentina; Caioli, Silvia; Zona, Cristina; Ciotti, Maria T.; Amadoro, Giuseppina; Calissano, Pietro (Frontiers in Cellular Neuroscience, 2017)
Alterations in NGF/TrkA signaling have been suggested to underlie the selective degeneration of the cholinergic basal forebrain neurons occurring in vivo in AD (Counts and Mufson, 2005; Mufson and Ginsbrg, 2008; Niewiadomska et al., 2011) and significant reduction of cognitive decline along with an improvement of cholinergic hypofunction have been found in phase I clinical trial in humans affected from mild AD following therapeutic NGF gene therapy (Tuszynski et al., 2005, 2015). Here, we show that the chronic (10-12 D.I.V.) in vitro treatment with NGF (100ng/ml) under conditions of low supplementation (0,2%) with the culturing serum-substitute B27 selectively enriches the basal forebrain cholinergic neurons (+36,36%) at the expense of other non-cholinergic, mainly GABAergic (-38.45%) and glutamatergic (-56.25%), populations. By taking advantage of this newly-developed septo-hippocampal neuronal cultures, our biochemical and electrophysiological investigations demonstrate that the early failure in excitatory neurotransmission following NGF withdrawal is paralleled by concomitant and progressive loss in selected presynaptic and vesicle trafficking proteins including synapsin I, SNAP-25 and a-synuclein. This rapid presynaptic dysfunction : (i) precedes the commitment to cell death and is reversible in a time-dependent manner, being suppressed by de novo external administration of NGF within 6 hr from its initial withdrawal ; (ii) is specific because it is not accompanied by contextual changes in expression levels of non-synaptic proteins from other subcellular compartments; (ii) is not secondary to axonal degeneration because it is insensible to pharmacological treatment with known microtubule-stabilizing drug such paclitaxel; (iv) involves TrkA-dependent mechanisms because the effects of NGF reapplication are blocked by acute exposure to specific and cell-permeable inhibitor of its high-affinity receptor. Taken together, this study may have important clinical implications in the field of AD neurodegeneration because it: (i) provides new insights on the earliest molecular mechanisms underlying the loss of synaptic/trafficking proteins and, then, of synapes integrity which occurs in vulnerable basal forebrain population at preclinical stages of neuropathology; (ii) offers prime presynaptic-based molecular target to extend the therapeutic time-window of NGF action in the strategy of improving its neuroprotective in vivo intervention in affected patients.